A Polyphonic Study of E.M. Forsters A Passage to India and George Orwell’s Burmese Days - Harith Ismael Turki; Dulfqar Mhaibes Abdulrazzaq (k@ta: A Biannual Publication on the Study of Languange and Literature, 2022)
The purpose of this study is to examine the multi-voicedness techniques in E.M. Forster’s A Passage to India and George Orwell’s Burmese Days, in terms of the narrator’s role and the plurality of voices and consciousnesses. This paper used the concept of polyphony which was coined by Bakhtin as a methodology in analyzing and examining the aforesaid novels. The results of this study showed that; First, both novels used the omniscient narrator as a narrative technique, since the voice of the author was evident on more than one occasion. Moreover, there was an influence by the omniscient narrator on the reader, which might be considered significant on more than one occasion, in controlling and manipulating his decisions and views in A Passage to India, while the influence was minuscule in Burmese Days. Second, this paper proved that the aforesaid novels are polyphonic ones. Finally, both authors gave a considerable margin of freedom for each character to express their ideologies freely.